THE EFFECT OF MSME CREDIT RESTRUCTURING, FINANCIAL TECHNOLOGY (FINTECH) INCLUSIVITY AND MSME COMPETITIVE ADVANTAGE ON MSME FINANCIAL PERFORMANCE IN THE NEW NORMAL PERIOD - Saeful Fachri; Heri Sapari Kahpi (SEAN Institute, 2022)
This research is quantitative to know the effect of MSME credit restructuring, financial technology (Fintech) inclusiveness, and MSME competitive advantage on MSME financial performance. The research object in this study is MSME actors divided into MSME centres in Serang City and District, Banten Province. The Partial Least Square Analysis method is an analytical technique used in this study. The study results show that: 1) Credit restructuring has a positive and significant effect on financial performance, 2) Financial technology inclusiveness has a positive and significant effect on financial performance, 3) Competitive advantage has a positive but not significant effect on financial performance